Características regionais sobre a ultra-estrutura das células principais do epitélio do ducto epididimal de Agouti paca - Orsi, Antonio Marcos; Simoes, Karina; Machado, Marcia Rita Fernandes; Domeniconi, Raquel Fantin (My University, 2009)
The principal (P) cells of epididymidis surface epithelium of Agouti paca were related to processes of adsorptive endocvtosis and phase-fluid endocvtosis, as well as protein secretion apparently also occur. These findings had been proposed on the base the cytoplasmic ultrastructural features of P cells in which were seen an expressive number of vesicles with several shapes, sizes and internalized content occurring also smaller pits and pale small vesicles located next to the apical brush border of microvilli. Moreover, occurred coated vesicles, smooth surface vesicles and great vesicles; multivesicular bodies, endosomes and lysosomes mainly viewed on supranuclear and apical positions. Presence of an appocrine secretory pathway was characterized in P cells through the occurrence of apical cytoplasmic expansions, protruding into the ducts epididymidis lumina) compartment.
Regional ultra structural features of principal cells from the epididymal epithelium lining of Agouti paca.